Analysis of Organic Vegetable Farmers Income During the Covid 19 Pandemic (Case Study of Aunupe Village, Wolasi Sub District, South Konawe District) - Ibrahim, Ikbal; Salam, Idrus; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aims to determine the income of farmers and the feasibility of farming organic vegetables in Aunupe Village, Wolasi Sub District, during the Covid 19 pandemic. The research was conducted in October-November 2020. The variables in this study included: Respondent identity, including (age, education, number of family dependents, farming experience), income indicators (land area, variable costs, fixed costs, production, revenue, and income). The population in this study were all organic vegetable farmers in Aunupe Village, Wolasi Sub District, Konawe Selatan District, 60 families with a sample of 38 households. The sample was determined by simple random sampling (Simple Random Sampling). The results showed that the income of organic vegetable farming in Aunupe Village, Wolasi Sub District during the Covid 19 pandemic in one production cycle (30 days) was IDR680,062 and the R / C ratio of organic vegetable farming was 3.28, so it is feasible to continue.